The effect of filler content and chemical modification on properties of polylactic acid/recycled low density polyethylene/nypa fruticans husk biocomposites - Mohamad Syahmie, Mohamad Rasidi (Universiti Malaysia Perlis (UniMAP), 2015)
Doctor of Philosophy in Materials Engineering